8-Quinolinyl Oxazoline: Ligand Exploration in Enantioselective Ni-Catalyzed Reductive Carbamoyl-Alkylation of Alkene to Access the Chiral Oxindoles - Luan, Baixue; Tang, Zaiquan; Wu, Xianqing; Chen, Yifeng (Synlett, 2022)
Chiral ligands play an essential role in transition-metal-catalyzed enantioselective transformations, in which chiral oxazoline-based scaffolds are the privileged chiral ligand. Nevertheless, 8-quinolinyl oxazoline (8-Quinox) ligands are underexplored in transition-metal-catalyzed asymmetric transformations since their development in 1998. Herein, we report an 8-Quinox ligand promoted Ni-catalyzed enantioselective reductive carbamoyl-alkylation of carbamoyl chloride tethered styrene with unactivated alkyl iodide, providing an expedient access to valuable enantioenriched oxindoles in good results.
Keywords: chiral ligand; nickel catalysis; reductive coupling; dicarbofunctionalization of alkene; oxindole